Primitive substitution tilings with rotational symmetries - Say-Awen, April Lynne D. (Animo Repository, 2018)
This work introduces the idea of symmetry order, which describes the rotational symmetry types of tilings in the hull of a given substitution. Definitions are given of the substitutions σ6 and σ7 which give rise to aperiodic primitive substitution tilings with dense tile orientations and which are invariant under six-and sevenfold rotations, respectively; the derivation of the symmetry orders of their hulls is also presented. © 2018 International Union of Crystallography.